Isometry of potential suture attachment sites for the medial aspect of the tibiotarsal joint - Jaeger, G. H.; Roe, S. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The isometry of the bipartite medial collateral ligament of the tarsus and two methods of stabilization by prosthetic ligament were assessed by measuring the change in distance between the origin and the insertion through full range of joint motion of the ligament and prosthetic ligaments. The single suture technique was isometric when the distal site was located at the centre of the trochlea of the talus. This site can only be used when the medial malleolus, which overlies the talus, is missing or removed. Whilst some length changes occur with hock motion, the double suture technique may be advocated in instances where the medial malleolus is present.
Keywords: Tarsus; collateral; ligament; isometry